Friction and wear behaviours of hard-coated/uncoated bearing steels under nano-additive oil lubrication - Sulaiman, Mohd Hafis; Nordin, Norhuda Hidayah; Sukindar, Nor Aiman; Dahnel, Aishah Najiah; Kamaruddin, Shafie (Springer, Singapore, 2022)
Tribological performance of bearing steels through the use of nano-additive oil lubrication and the hard-coated surfaces was studied. Hard coatings like DLC, TiAlN and CrN were deposited onto the bearing steels using Physical Vapour Deposition (PVD) technique. The tribological experiment was performed in accordance to ASTM G77 test method by using block-on-ring test. The test parameters include an incremental loading pressed on the sliding surfaces in a range of 0 N to 60 N, and the effect of interface temperature was investigated. All bearing steels functioned satisfactorily with low friction under very, thin nano-additive oil film. The hard-coated bearing steels enhanced the wear performance in comparison to that of a finely polished bearing steel. The interface temperature increases with the wear damage, whereby the mating sliding surface prone to severe adhesive wear at larger contact loadings.